The Impact of the Krueng Keureuto Dam and Reservoir on Flood Management in Aceh Utara Regency and Surrounding Areas: A Literature Review - Yusrawati; Mawar Hayati; Fitriani Agustina; Masyudi (Universitas Serambi Mekkah, 2024)
Flood disasters are a long-standing problem in North Aceh Regency and its surroundings, causing serious losses both material and non-material. To overcome this problem, the government has built the Krueng Keureuto Dam and Reservoir as part of its flood management strategy. However, the actual impact of this project on flood mitigation needs to be evaluated through a comprehensive literature review. This study aims to analyze the effectiveness of the construction of the Krueng Keureuto Dam and Reservoir on flood mitigation efforts in North Aceh Regency and its surroundings. From this literature review, it was identified that factors causing the ineffectiveness of the Krueng Keureuto Dam and Reservoir in flood prevention efforts in North Aceh Regency include non-routine sedimentation management, less stringent environmental protection, low participation and awareness of community behavior to prevent flooding and low inter-institutional coordination. This project has not fully met expectations in flood mitigation, but still has the potential to provide significant benefits if further elaborated. The author's recommendations for increasing the effectiveness of dams and reservoirs for flood mitigation include strengthening river sedimentation management, increasing environmental monitoring, community participation campaigns in reservoir maintenance and management, as well as expanding cooperation between the government and the private sector. Follow-up plans will involve regulatory updates, infrastructure improvements, as well as educational programs to increase public awareness about flood management.